In vitro selection of ribozymes dependent on peptides for activity - ROBERTSON, MICHAEL P. (Copyright 2004 by RNA Society, 2004)
A peptide-dependent ribozyme ligase (aptazyme ligase) has been selected from a random sequence population based on the small L1 ligase. The aptazyme ligase is activated > 18,000-fold by its cognate peptide effector, the HIV-1 Rev arginine-rich motif (ARM), and specifically recognizes the Rev ARM relative to other peptides containing arginine-rich motifs. Moreover, the aptazyme ligase can preferentially recognize the Rev ARM in the context of the full-length HIV-1 Rev protein. The only cross-reactivity exhibited by the aptazyme is toward the Tat ARM. Reselection of peptide- and protein-dependent aptazymes from a partially randomized population yielded aptazymes that could readily discriminate against the Tat ARM. These results have important implications for the development of aptazymes that can be used in arrays for the detection and quantitation of multiple cellular proteins (proteome arrays).